How teacher behaviors and perceptions, air change rates, and portable air purifiers affect indoor air quality in naturally ventilated schools - Xia, Tian; Raneses, Julia; Schmiesing, Brixon; Garcia, Raquel; Walding, Alison; DeMajo, Richardo; Schulz, Amy; Batterman, Stuart A. (Frontiers in Public Health, 2024)
Introduction Many school buildings have inadequate ventilation, rudimentary if any air filtration, and aging and poorly maintained mechanical systems, all of which can lead to poor indoor air quality (IAQ). These issues are especially acute in environmental justice (EJ) communities where schools are located in polluted areas. This community-based participatory research examines how IAQ in naturally ventilated school buildings is affected by the use of air purifiers, air change rates, outdoor pollution levels, and teacher and staff behavior. Methods IAQ assessments were performed at two schools in Detroit, Michigan, which included building walk-through inspections and continuous indoor and outdoor measurements of black carbon (BC), particulate matter (PM10 and PM2.5), carbon dioxide (CO2), air change rates (ACRs), temperature, humidity, and sound pressure levels. Air purifiers with usage monitors were then installed, and the IAQ assessments were repeated. Teachers were surveyed before and after purifier deployment. Results At baseline, classrooms had low ACRs (0.58–1.38 h−1), moderate PM2.5 levels (2.8–8.9 μg/m3), highly variable PM10 concentrations (4.7–37.5 μg/m3), and elevated BC levels (0.3–0.7 μg/m3), reflecting emissions from local traffic, industry and other sources. The installation and use of purifiers reduced pollutant levels and the overall performance matched the predictions of a single compartment model. However, daily reductions varied widely among classrooms, reflecting differences in teacher behavior regarding the frequency of opening windows and the operation of purifiers, including differences in purifier fan speed settings and whether purifiers were used at night. Survey responses indicated that many teachers were aware of IAQ problems. The higher rates reported for health symptoms and dissatisfaction at one school may have lowered the teachers’ tolerance to noise and reduced purifier use. Discussion The study helps explain the variation reported in prior studies using purifiers, and it reinforces the need to monitor IAQ and purifier use, use enhanced filtration and increase ventilation, and engage with teachers and school staff to support and maintain IAQ programs in schools.